Evaluation of Dentists' Proficiency in Emergency Management of Permanent Tooth Injuries: A Cross-sectional Study - Abdullah, Arig; ElGatlawi, Ghada; Bensaleem, Belkays; Husay, Ayyah; , Marwa Mustafa; , Alaa Imqadaa; Sabrin Abdul-Al-Wakil, (AlQalam Journal of Medical and Applied Sciences, 2025)
Traumatic dental injuries represent a significant public health concern, impacting individuals across all age groups and accounting for 20-30% of permanent dentition injuries worldwide. The primary causes include accidental falls, sports, and traffic accidents, with consequences such as pulp necrosis, root resorption, and compromised quality of life. Effective emergency management is critical to improving outcomes, yet knowledge gaps among healthcare providers remain a challenge. This study evaluates the knowledge, attitudes, and practices of Libyan dentists in Benghazi regarding the emergency management of TDIs in permanent teeth. A cross-sectional study was conducted between August and October 2024, involving 260 dental practitioners in Benghazi. Data were collected using a validated, self-administered questionnaire based on International Association of Dental Traumatology guidelines. The survey assessed demographic variables, self-evaluated knowledge, and practical approaches to managing common dental injuries. Statistical analyses were performed using SPSS and R software. The majority of participants were under 40 years old (83.8%), with 53.5% being general dentists. Most worked in private clinics (58.8%), and 68.1% demonstrated a good level of knowledge about TDI management. However, 31.9% exhibited insufficient understanding, particularly regarding complex injuries. Despite this, 96.2% reported positive practices in emergency care, underscoring their commitment to patient outcomes. While most dentists in Benghazi exhibit adequate knowledge and positive practices in managing TDIs, gaps remain in handling complex cases. This study highlights the need for targeted training programs to enhance practitioners' proficiency and ensure optimal care for dental trauma patients. تُمثل إصابات الأسنان الرضحية مصدر قلق كبير على الصحة العامة، إذ تؤثر على الأفراد من جميع الفئات العمرية، وتُمثل ما بين 20% و30% من إصابات الأسنان الدائمة في جميع أنحاء العالم. تشمل الأسباب الرئيسية السقوط العرضي، والحوادث الرياضية، وحوادث المرور، مع عواقب مثل نخر اللب، وامتصاص الجذور، وتدني جودة الحياة. تُعد الإدارة الفعالة للطوارئ أمرًا بالغ الأهمية لتحسين النتائج، إلا أن فجوات المعرفة بين مُقدمي الرعاية الصحية لا تزال تُمثل تحديًا. تُقيّم هذه الدراسة معارف ومواقف وممارسات أطباء الأسنان الليبيين في بنغازي فيما يتعلق بالإدارة الطارئة لإصابات الأسنان الرضحية في الأسنان الدائمة. أُجريت دراسة مقطعية بين أغسطس وأكتوبر 2024، شارك فيها 260 طبيب أسنان في بنغازي. جُمعت البيانات باستخدام استبيان مُعتمد ذاتيًا، استنادًا إلى إرشادات الجمعية الدولية لطب إصابات الأسنان. قيّم المسح المتغيرات الديموغرافية، والمعرفة المُقيّمة ذاتيًا، والأساليب العملية لإدارة إصابات الأسنان الشائعة. أُجريت التحليلات الإحصائية باستخدام برنامجي SPSS وR. كانت غالبية المشاركين دون سن الأربعين (83.8%)، وكان 53.5% منهم أطباء أسنان عامين. عمل معظمهم في عيادات خاصة (58.8%)، وأظهر 68.1% منهم مستوى جيدًا من المعرفة بإدارة إصابات الأسنان المزمنة. ومع ذلك، أظهر 31.9% منهم فهمًا غير كافٍ، لا سيما فيما يتعلق بالإصابات المعقدة. على الرغم من ذلك، أفاد 96.2% بممارسات إيجابية في رعاية الطوارئ، مما يؤكد التزامهم بتحقيق نتائج مرضاهم. في حين أن معظم أطباء الأسنان في بنغازي يتمتعون بمعرفة كافية وممارسات إيجابية في إدارة إصابات الأسنان المزمنة، إلا أنه لا تزال هناك فجوات في التعامل مع الحالات المعقدة. تُسلط هذه الدراسة الضوء على الحاجة إلى برامج تدريبية مُستهدفة لتعزيز كفاءة الممارسين وضمان رعاية مثالية لمرضى صدمات الأسنان